2018
DOI: 10.1186/s12886-018-0815-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and prognostic factors for aggressive posterior retinopathy of prematurity following initial treatment with intravitreal ranibizumab

Abstract: BackgroundThis study sought to identify factors associated with retinal detachment and retreatment of aggressive posterior retinopathy of prematurity (APROP) initially treated with intravitreal ranibizumab (IVR) injection as well as the efficacy of IVR treatment.MethodsThis was a retrospective study. A total of 83 preterm infants (160 eyes) diagnosed with APROP who were primarily treated with IVR were included. The 160 eyes were divided into two groups based on the anatomic outcomes. Group A included 35 eyes t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 36 publications
0
16
0
Order By: Relevance
“…Based on ROP classification, recurrence was seen in 70 of 105 (67%) eyes with APROP, 157 of 411 (38%) eyes with type 1 ROP, and 18 of 113 (16%) eyes with prethreshold ROP. Higher rates of recurrence in eyes with APROP have previously been noted in patients receiving either intravitreal ranibizumab34 or bevacizumab44 with low birthweight as a common risk factor for APROP recurrence and retreatment. Feng et al33 also noted that the rate of recurrence was significantly higher in patients with zone I ROP (61%, 101 of 164 eyes) than in zone II ROP (31%, 144 of 465 eyes).…”
Section: Risk Of Recurrence Of Rop Treated With Ranibizumabmentioning
confidence: 85%
See 2 more Smart Citations
“…Based on ROP classification, recurrence was seen in 70 of 105 (67%) eyes with APROP, 157 of 411 (38%) eyes with type 1 ROP, and 18 of 113 (16%) eyes with prethreshold ROP. Higher rates of recurrence in eyes with APROP have previously been noted in patients receiving either intravitreal ranibizumab34 or bevacizumab44 with low birthweight as a common risk factor for APROP recurrence and retreatment. Feng et al33 also noted that the rate of recurrence was significantly higher in patients with zone I ROP (61%, 101 of 164 eyes) than in zone II ROP (31%, 144 of 465 eyes).…”
Section: Risk Of Recurrence Of Rop Treated With Ranibizumabmentioning
confidence: 85%
“…A recent Cochrane review in 2018 concluded that there was insufficient evidence to provide a strong conclusion for the routine use of intravitreal anti-VEGFs in clinical practice 23. To date, eight head-to-head studies19,2431 have been published comparing intravitreal ranibizumab to intravitreal bevacizumab and/or conventional laser photocoagulation for ROP and three retrospective studies3234 with at least 100 eyes have been published on outcomes of infants treated intravitreal ranibizumab monotherapy (Table 2).…”
Section: Current Literature On Ranibizumab For Ropmentioning
confidence: 99%
See 1 more Smart Citation
“…Six weeks was taken as the benchmark for deferred laser, as most cases of recurrence or reactivation after initial IVR tend to occur after 6 weeks. [ 13 14 15 ] The infants in group 2 were Followed up weekly to monitor the growth of retinal vessels and recurrence of plus disease or appearance of peripheral retinopathy. The laser was done using Diode laser indirect ophthalmoscope (Iridex ® Germany) under topical anesthesia in NICU after obtaining written informed consent from the parents.…”
Section: Methodsmentioning
confidence: 99%
“…[ 10 11 12 ] Unfavorable structural outcomes and late recurrence of disease and thus need for longer follow-up are common issues with anti-VEGF monotherapy. [ 10 13 14 15 ] To overcome the disadvantages of conventional laser as well as anti-VEGF monotherapy, combined treatment has been evaluated in infants with Zones I and II ROP, which showed promising anatomical outcomes. [ 12 ] Similarly, outcomes of rescue laser after initial treatment with anti-VEGF therapy had also shown good results in APROP.…”
mentioning
confidence: 99%